OP0099 Safety, tolerability and initial signs of efficacy of the fully human immunocytokine DEKAVIL (F8IL10): a novel therapeutic approach for rheumatoid arthritis. (15th June 2017) - Galeazzi, M; Sebastiani, G; Voll, R; Wollenhaupt, J; Viapiana, O; Dudler, J; Selvi, E; Baldi, C; Bardelli, M; Bannert, B; Finzel, S; Specker, C; et al.
Abstract : Background: The antibody-based targeted pharmacodelivery of cytokines by means of immunocytokines has the potential to enhance therapeutic activity at the site of disease while sparing healthy tissues. Dekavil (F8IL10) is a fully human immunocytokine composed of the vascular targeting antibody F8 (specific to EDA) fused to the cytokine interleukin-10. Dekavil is currently in phase II clinical development for the treatment of rheumatoid arthritis (RA). Objectives: In the phase Ib dose escalation study, the primary objective was to explore safety, tolerability and the maximum tolerated dose of Dekavil when administered in combination with methotrexate (MTX). The aim of the currently ongoing phase II study is to assess therapeutic activity of Dekavil plus MTX over MTX alone by measuring the mean change from baseline of DAS28-CRP. Immunogenicity of F8IL10 and its PK and PD profile will also be explored. Methods: Patients with active RA despite MTX therapy and who failed anti-TNF treatment are the target population of both studies. In the phase Ib trial, cohorts of 3–6 patients were treated with escalating doses of Dekavil (6, 15, 30, 60, 110, 160, 210, 300, 450 and 600 μg/kg) in combination with a fixed dose of MTX (10–15 mg). In the multicenter, double-blind, placebo-controlled phase 2 study, patients are randomized into two treatment groups (Dekavil 30 or 160 μg/kg plus MTX) and one placebo group (placebo plus MTX). Dekavil is administered once weekly by s.c. injection for a maximum of 8 weeks in both studies. Results: Dekavil has been shown to be well tolerated up to the highest investigated dose (600 μg/kg) and an MTD was not reached. In 33 out of 34 patients treated in the phase 1 study, no DLTs, no SAEs and no SUSARs have been reported. One patient in cohort 9 (450 μg/kg) experienced a DLT (G2 purpura) and a SAE (G2 dyspnea, not drug related). The patient received corticosteroids and fully recovered within one week. Mild injection site reactions were the most frequently observed adverse events and occurred in 62% of the patients. Furthermore, two cases of drug related anemia (G2 and G3) were reported in this study. All adverse reactions resolved completely. At the first efficacy assessment after 4 cycles of treatment, 48% of evaluable patients (16/33) revealed ACR and/or EULAR responses. The fraction of responding patients increased to 57.7% (15/26) after 8 cycles of treatment. Two patients benefited from ACR70 responses for more than 12 months after the last drug administration. As of January 2017, 22 out of 87 patients have been treated in the phase 2 clinical study and neither SUSAR nor treatment-related deaths were recorded. Conclusions: The currently available data suggest that Dekavil is a safe and promising novel therapeutic for the treatments of RA. Disclosure of Interest: M. Galeazzi: None declared, G. Sebastiani: None declared, R. Voll: None declared, J. Wollenhaupt: None declared, O. Viapiana: None declared, J. Dudler: None declared, E. Selvi: None declared, C. Baldi: None declared, M. Bardelli: None declared, B. Bannert: None declared, S. Finzel: None declared, C. Specker: None declared, P. Sarzi Puttini: None declared, F. Bootz Employee of: Philochem AG, D. Neri Shareholder of: Philogen SpA